SEBARAN JEJAK MACAN TUTUL DI KAWASAN HUTAN LINDUNG GUNUNG TIKUKUR KPH BANDUNG SELATAN - Billy Anugrah Gymnastiar (Fakultas Kehutanan Universitas Winaya Mukti, 2019)
The Javan leopard (Panthera pardus) is an endemic species to Java and currently classified as critically endangered species on IUCN Red List, since there possibly even less than 100 left in the wild. One of habitat of Javan leopard is Protected Forest Area of Tikukur Mountain KPH Bandung Selatan. The object of research is to find out the existence signs, map the distribution, and describe the findings of leopard’s prey and any disturbances that occur to the java leopard in the Protected Forest Area of Tikukur Mountain KPH Bandung Selatan. The method of research are preliminary research and intensive research. Preliminary research was by interview, while intensive research by transect and album camera trap method. Based on the research, the number of leopard presence signs are one voice heard and two feces found. The existence of java leopard in the Protected Forest Area of Tikukur Moutain KPH Bandung Selatan is horizontally spread in 2 types of land use, namely forests and plantations. It vertically spreads at altitude of 1445-1617 masl with a sloping and sloping slope. The prey found are java langurs, partridge, and pigs. The disturbances occurred to the java leopard in the protected forest area of Tikukur mountain are in the form of PHBM, military training, hunting, and other activities namely, climbing activities.